The Comparison of life satisfaction, coping styles and resilience in divorced bidder and non-bidder women - Faramarz Asanjarani; Nasim Galehdarpour; Fereshte Hasani Estalkhi; Mohammad Delavar Neghabi; Abbas Shahverdi; Solmaz Rajamand (Shahid Beheshti University of Medical Sciences, 2017)
Background: The basis and pillar of the family as the most important part of society is marriage. Marriage and family service for the creation of a center comfort and well-being and vitality. However, the focus of comfort sometimes uneasy marriage and divorce. This study of life satisfaction, coping styles and resilience in divorced and non-divorced women bidder divorce. Materials and methods:This research method is causal-comparative. The instrument used coping styles questionnaire, a questionnaire was Resilience and Life Satisfaction. Analysis of data using multivariate analysis of variance was performed and software SPSS-22. Results: The results showed that the two groups of bidders and bidders divorce signifiant difference in terms of life satisfaction (F=10.9, P>0.01), Problem-focused coping styles (F=8.7, P>0.01), emotionfocused coping styles (F=10.0, P>0.01), avoidance coping style circuit (F=3.8, P>0.01), resilience (F=19.5, P>0.01) there. Conclusion: This study showed that women bidder divorce from life satisfaction, coping styles and resiliency than women bidder divorce. Using the fidings of this study can be set-tasks for psychotherapy and counselling especially for women bidder's divorce.